Optimization Design Analysis of Boiler Blowdown Utilization on A Rotary Coal Dryer with Drum Tilt Angle Variations - Alvin Mizrawan Tarmizi; Bambang Arip Dwiyantoro; Aripin Gandi Marbun (JMES The International Journal of Mechanical Engineering and Sciences, 2022)
Lignite coal has dominated the use of steam power plants in recent years. Despite the consequences, which cause many problems, lignite is cheap and easy to obtain. One of the problems was mitigated by reducing the moisture content using a rotary coal dryer. Coal dryer is deemed uneconomical with the current energy sources from turbine extraction steam, electric heaters, and exhaust gas using large-powered fans. The waste energy from boiler blowdown, a water-vapored ﬂuid discharged from the boiler to maintain water and steam quality, is being conducted to improve. Blowdown investigated in a rotary coal dryer type. The compressed air absorbed the heat from the blowdown through the steam coil. The hot air mixed with the coal in the rotary drum. A rotary drum was tested with the tilt angles of 0°, 10°, 20°, 30°, 40°, 50°, 60°, 70°, 80°, and 90°. The research steps were designing, preliminary modeling, numerical analysis, prototyping, and experimental performing. The result shows that the moisture content has decreased signiﬁcantly from 35.37% to 21.28%, within an angle of 10°. Based on an economic assessment, this coal dryer also proves that dried lignite coal has increased 4.9% economic value than bituminous coal.